Exploring The Frontier Of Non-coding RNAs: Biogenesis, Functional Diversity, And Disease Associations Of CircRNAs And TinyRNAs - ÇALIŞIR, HİLAL-NUR; AKÇAY, SILA; ENES, BAL; KILBAŞ, PELİN ÖZFİLİZ; BUSE, ÖZDEN; ŞAHİN, BURCU AYHAN (Springer Science and Business Media B.V., 2025)
Non-coding RNAs (ncRNAs) represent a pivotal frontier in molecular biology, expanding our understanding of genetic regulation beyond the classical central dogma. Among these, circular RNAs (circRNAs) and tiny RNAs (tyRNAs) have emerged as critical regulators with diverse roles in gene expression, cellular homeostasis, and disease pathogenesis. CircRNAs, characterized by their covalently closed structures, exhibit remarkable stability and functional versatility, including acting as microRNA sponges, transcriptional regulators, and protein scaffolds. Tiny RNAs, a newly recognized class of ncRNAs, are implicated in post-transcriptional regulation through interactions with Argonaute proteins, influencing pathways from viral defense to neurodegenerative diseases. This review synthesizes recent advancements in the biogenesis, molecular mechanisms, and clinical significance of circRNAs and tyRNAs, highlighting their potential as biomarkers and therapeutic targets in cancer, metabolic disorders, and neurological conditions. By exploring their unique regulatory landscapes, this work aims to inspire further research into the ncRNA universe and its implications for human health.
Keywords: Biomarkers and therapeutic targets; Circular RNA (circRNA); Gene expression regulation; Noncoding RNA (ncRNA); Tiny RNA (tyRNA)